Evaluation of the mental health status of community frontline medical workers after the normalized management of COVID-19 in Sichuan, China - Xu, Xiaoru; Zhang, Jianshu; Fang, Ronghua; Liu, Hong; Zhou, Weihua; She, Yi; Liu, Feng; Hong, Xia; Deng, Xuexue (Frontiers in Psychiatry, 2023)
Background: During the coronavirus disease 2019 (COVID-19) pandemic, community medical workers, as the primary enforcers of community control measures, undertook many tasks with high exposure risk, resulting in severe psychological pressure, anxiety, depression and other psychological problems. Gender, type of workers, education, marital status, working years and other demographic factors were affect the mental state of medical workers. Community frontline medical workers gradually returned to normal work and life after the normalized management of COVID-19, but heavy work and high psychological pressure may continue to affect them. Thus, our research team used the same psychological questionnaire to investigate the psychological status of community frontline medical workers after the normalized management of COVID-19 compared with the COVID-19 period.: This was a cross-sectional study of community frontline medical workers in Sichuan, China, from February 6 to 17, 2023. Symptom Checklist-90 (SCL-90) and a self-designed questionnaire of demographic characteristics were provided to the participants point-to-point through a mobile network platform. Multiple logistic regression was used to analyse influencing factors related to community frontline medical workers' psychology. Results: A total of 440 valid questionnaires were statistically analysed, including 192 (43.64%) from doctors and 248 (56.36%) from nurses. There were 222 (50.45%) participants who were SCL-90 positive. The median total SCL-90 score of medical workers was 105.0 (IQR 95.00-123.75), which was higher than that during the COVID-19 period. The doctor's median SCL-90 score was 108.5 (IQR 96.00-136.25), and the positive item score was 16.5; the nurse's median score was 104.0 (IQR 94.00-119.50), and the positive item score was 12.0. Bachelor's degree education, no fixed contract and working years (10-19 years, 20-29 years, 30-39 years) were independent influencing factors for community frontline medical workers' psychology.After the normalized management of COVID-19, community frontline medical workers still suffered from psychological problems that were even more serious than those during COVID-19. Doctors were more likely to have psychological problems than nurses. In addition, the mental health status of community frontline medical workers was affected by education, type of contract and working years.Managers should pay attention to the mental health of these people.